School environmental education in the face of the climate emergency: the Biotechnology plan itinerary as praxis space - Fornazari, Valéria Brumato Regina; Canazart , Daniele Araujo (Technical and Scientific Journal Green Cities, 2025)
Objective – The present work aimed to produce and apply an investigative didactic sequence (DS), addressing state propositions for the Biotechnology curricular component, with the aim of promoting critical environmental education on the climate emergency.Methodology – Collaborative action research was carried out with 27 high school students from a public school, in the Biotechnology Training Itinerary. Data collection occurred through a structured questionnaire, participant observation and field diary recording. Data analysis was carried out based on Bradin's Content Analysis (1977).Originality/Relevance – The proposition and analysis of an investigative didactic sequence, based on the Learning Path of the Biotechnology Formative Itinerary, which presents itself as a rigid proposal, with critical environmental education reflecting on environmental emergency.Results – Initially, the students had a reductionist and alienating view on the climate crisis and biotechnology, with little connection to current science. Throughout the didactic sequence, students were able to correlate the anthropogenic factor as the origin of the climate crisis, in addition to understanding the possible adaptations and mitigation measures for the crisis.Theoretical/Methodological Contributions – The methodological implications involve the use of an investigative didactic sequence applied in the Formative Itinerary based on Learning Paths, providing a pedagogical practice grounded in critical environmental education, despite the curricular limitations of the Formative Itineraries.Social and Environmental Contributions - The research contributes to the formation of environmentally responsible and critical citizens, being a step toward social transformation in the face of the climate emergency. The social implications involve raising students' awareness about the climate crisis and biotechnology, and their potential solutions in the current context.
Keywords: New High School; Environmental Crisis; Teaching and Learning Strategy